2010
DOI: 10.1007/s10534-010-9293-5
|View full text |Cite
|
Sign up to set email alerts
|

HIV therapeutic possibilities of gold compounds

Abstract: Highly active antiretroviral therapy (HAART) has resulted in decreased mortality and morbidity from the acquired immune deficiency syndrome caused by the human immunodeficiency virus (HIV). Drug resistance and toxicity of HAART has led to the search for novel inhibitors of HIV infection. Gold-based compounds have shown promising activity against a wide range of clinical conditions and microorganism infections including HIV-1. A typical example is auranofin which resulted in an elevated CD4? T-cell count in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…Gold starting material, HAuCl 4 .4H 2 O, was synthesised using procedures reported by Block, 1953 [27] and bis(thiosemicarbazone) ligands (L1-L4) according to methods by West et al, 1997 [28]. All the solvents were purchased from Merck and dried using conventional methods.…”
Section: Reagents Starting Materials and Instrumentationmentioning
confidence: 99%
“…Gold starting material, HAuCl 4 .4H 2 O, was synthesised using procedures reported by Block, 1953 [27] and bis(thiosemicarbazone) ligands (L1-L4) according to methods by West et al, 1997 [28]. All the solvents were purchased from Merck and dried using conventional methods.…”
Section: Reagents Starting Materials and Instrumentationmentioning
confidence: 99%
“…A further promising new area of application for goldbased drugs was recently reported by Fonteh et al and Lewis et al, who obtained initial promising results when gold(I) phosphine compounds were applied against HIV [106][107][108]. The potential of gold as a novel therapeutic approach for autism was recently highlighted [109].…”
Section: Gold-based Pharmaceuticalsmentioning
confidence: 96%
“…Unfortunately, anti-retroviral therapy often has severe side effects and does nothing to eliminate the viral reservoir in patients. Thus, the key to curing HIV would need to include eradicating the virus from the body (Fonteh et al 2010). The persistence of HIV in treated patients is partially due to the infection of short-term memory CD4 ?…”
Section: Ros-mediated Effectsmentioning
confidence: 99%
“…T cells by inhibiting lymphoblastogenesis, and this low CD4 ? T cell count is often an indication of the severity of the disease and is correlated with poor survival outcomes (Shapiro and Masci 1996;Fonteh et al 2010). The first report indicating that AF may be useful in the treatment of HIV was by Shapiro and Masci (1996), who reported that in an HIV-infected patient treated with AF for psoriatic arthritis, the psoriatic arthritis symptoms improved but remarkably the patient's CD4 ?…”
Section: Ros-mediated Effectsmentioning
confidence: 99%